Labor Contracts with Voluntary Quits - Ito, Takatoshi (Journal of Labor Economics, 1988)
This paper considers labor contracts between the risk-neutral firm and risk-averse workers with heterogeneous outside opportunities (alternative wages), which become known to the worker after a costly on-the-job search. In the case of a deterministic alternative wage, self-selection over a menu of contract wages would achieve the first-best contract. If the alternative wages are stochastic, the second-best contract emerges as a trade-off between productive efficiency and risk sharing. Workers who voluntarily search are fewer, and workers who search are less likely to quit. If the search effort is not monitored, even fewer workers search.